Using Context as an Assist in Word Solving: The Contributions of 25 Years of Research on the Interactive Strategies Approach. (16th September 2020) - Scanlon, Donna M.; Anderson, Kimberly L.
ABSTRACT: Recently, there has been growing concern about how to most effectively support the literacy development of beginning and struggling readers with regard to helping them learn to effortlessly identify the huge number of words that proficient readers ultimately learn to read with automaticity. Some, noting the critical importance of phonics instruction in learning to read in an alphabetic writing system, take the position that students should attend only to alphabetic information in word‐solving attempts. However, long‐standing theories of the development of word‐reading skills support the value of teaching students to use both alphabetic and contextual information in word solving in interactive and confirmatory ways. The authors summarize 25 years of research in which beginning and struggling readers were taught to use both code‐ and meaning/context‐based strategies for word solving and were provided with explicit, responsive instruction focused on the alphabetic code. The authors present brief summaries of theoretical explanations of the word‐learning process. Then, the authors summarize six experimental studies that, together, included students in kindergarten through fourth grade and involved the implementation of the Interactive Strategies Approach in the primary grades and an extension of the approach with middle elementary students with reading difficulties. The studies resulted in substantially improved reading outcomes among treatment versus business‐as‐usual groups. The authors contend that using both phonics‐ and context‐based information facilitates the ability to build sight vocabulary, which in turn enables readers to turn their attention to the most important goal of literacy learning: meaning construction.